The Rise of the Right in Times of Capitalist Crisis: A Materialist Explanation - Rutar, Tibor (Identities: Journal for Politics, Gender and Culture, 2015)
In the article we aim to examine two pressing issues for any progressive, anti-capitalist movement or party today. The first concerns the (non-)success of classical Marxist attempts at providing a satisfactory account of workers’ rising support for pro-capitalist ideology and political parties in times of economic crisis. The second relates to an updated attempt of a materialist explanation of this phenomenon. Author(s): Tibor Rutar Title (English): The Rise of the Right in Times of Capitalist Crisis: A Materialist Explanation Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 84-99 Page Count: 15 Citation (English): Tibor Rutar, “The Rise of the Right in Times of Capitalist Crisis: A Materialist Explanation,” Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015): 84-99.